2016
DOI: 10.17015/ejbe.2016.017.02
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Personal Attitude, Subjective Norm, and Perceived Behavioural Control on Entrepreneurial Intentions of Women

Abstract: In the last decade, female entrepreneurship has been identified as one of the most

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
40
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 27 publications
17
40
1
7
Order By: Relevance
“…However, training, education, and business experience can relax the credit constraint to a great extent. The performance of women entrepreneurs or the starting of new business is significantly influenced by entrepreneurial intention which is also influenced by personal attitude and behavioral control (Dinc & Budic, 2016). The study of Celebioglu (2017) shows that gender inequality affects the women employment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, training, education, and business experience can relax the credit constraint to a great extent. The performance of women entrepreneurs or the starting of new business is significantly influenced by entrepreneurial intention which is also influenced by personal attitude and behavioral control (Dinc & Budic, 2016). The study of Celebioglu (2017) shows that gender inequality affects the women employment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To measure PBC, we used a six item scale (Dinc & Budic, ). Sample items included, “To start a firm and keep it working would be easy for me,” “I can control the creation process of a new firm,” “If I tried to start a firm, I would have a high probability of succeeding.” The value of Cronbach's alpha is 0.9.…”
Section: Methodsmentioning
confidence: 99%
“…To start a firm and keep it working would be easy for me Dinc and Budic (2016) I am prepared to start a viable firm I can control the creation process of a new firm I know the necessary practical details to start a firm I know how to develop an entrepreneurial project If I tried to start a firm, I would have a high probability of succeeding Entrepreneurial intention I am ready to do anything to be an entrepreneur Liñán and Chen (2009) My professional goal is to become an entrepreneur I will make every effort to start and run my own firm I am determined to create a firm in the future I have very seriously thought of starting a firm I have the firm intention to start a firm someday…”
Section: Perceived Behavioral Controlmentioning
confidence: 99%
“…This study was conducted based on the previous research (Dinc & Budic, 2016) which found that personal attidude and perceived behavioral control gave significant impact on entrepreneurial intention but that research along with other previous researches related to the relationship between theory of planned behavior and entrepreneurial intention (Sequeira et al, 2007;Fenech et al, 2019;Hsu et al, 2018) had been conducted solely based on the concept of entrepreneurship in general, it was rarely seen from the perspective specific to ecommerce. Thus, this study specifically aimed to see the impact of theory of planned behavior towards student's intention to practice online business.…”
Section: Hypothesis Developmentmentioning
confidence: 99%